Aplikasi Pedoman Hidup Islami Warga Muhammadiyah Berbasis Dekstop Bagi Dosen dan Karyawan Universitas Muhammadiyah Bengkulu - Dandi Sunardi; Muhammad Husni Rifqo; Muntahanah Muntahanah; Anisyah Oktariani Supriyadi (UNIVED Press, 2024)
As a university under the auspices of the Muhammadiyah organization, the Muhammadiyah Islamic Life Guidelines (PHIWM) is a basic guide in daily life for lecturers and employees of Universitas Muhammadiyah Bengkulu (UM Bengkulu). The problem in this research is that not all lecturers and employees of Universitas Muhammadiyah Bengkulu have PHIWM books. This research aims to circulate this PHIWM application among lecturers and employees and of course make it easier for those who do not have a book and help practice the material in the book in the surrounding environment. The research method used in this research is qualitative. The development of this system includes the waterfall method and data collection methods such as interviews, literature reviews, observations, and literature studies. The results of testing the application obtained from black box testing that the application can run well without any errors so that the application is feasible to use and is very helpful for lecturers and employees who do not have a PHIWM book before now the PHIWM application is made. With the application, it is easy to access anywhere and anytime, especially using a laptop / PC.